Effect of insecure environment on the academic performance of female students in Pakistan - Zareen, Mahwash (Psychology, Evaluation, and Technology in Educational Research, 2020)
The study investigated the effect of an insecure city environment on the academic performance of female college students in Pakistan. Although studies are found in the insecure environment inside the institute, none investigated the insecure environment on the ways from home to college. This research specifically targeted female students of the age from 14 to 16 years who walked to their colleges and often experience unusual activities or harassment affecting their academic performance.100 Females who were studying in the Government institutes, were the desired sample of the current study who were studying at the government colleges and were students of 1st year. The result indicated that an insecure city environment is a significant negative predictor of academic performance among female college students who are attending Government colleges in Pakistan (Î²= -.81, p < .001). The findings drawn from this study are likely to help save the young female students from developing insecure feelings while moving on the road alone. This research helps in providing a secure environment for the female to ensure their optimized learning. This is ascertained through a better future by instigating some action planning for providing the females with a safe environment that promotes effective learning.